RELATIONSHIP BETWEEN WATER QUALITY AND ABUNDANCE OF CYANOPHYTA IN PENJALIN RESERVOIR - Badrun Mahera Agung; Agatha Sih Piranti; Carmudi Carmudi (UPT Penerbitan Universitas Jember, 2016)
Cyanophyta (blue green algae) is one of the divisions of phytoplankton, microscopic aquatic organisms that some of them is harmful because secrete toxins and cause blooming so polluted waters. The purpose of this study was to determine the water quality in the Penjalin Reservoir in terms of physical and chemical parameters, determine abundance of Cyanophyta in Penjalin Reservoir, as well as determine the relationship between water quality with an abundance of Cyanophyta in order to control the blooming of Cyanophyta in Penjalin Reservoir. The method applied in this research is survey. The analytical method used to determine the water quality is descriptive method with table. Abundance of Cyanophyta were analyzed qualitatively and quantitatively. The relationship between physics and chemistry waters with an abundance of Cyanophyta were analyzed using correlation analysis. The results of the research in the waters of the Penjalin Reservoir obtained 25 species of Cyanophyta abundance ranged from 838.16 to 1322.77 ind.l-1, with the highest species abundance owned by Microcystis sp. Diversity index values ranged from 0.7 to 2.15 indicate that the diversity of Cyanophyta is classified, and the dominance index value of 0.009 to 0.29 indicates that no species dominates. Cyanophyta abundance in the waters of the Penjalin Reservoir 37,89% influenced by parameter TDS and Total P (r = 0,501) with equation Y = -701,5 + 33,4 (TDS) + 919,7 (Total P). Water quality in Penjalin Reservoir still within the range of good and decent for the life of organisms present in the reservoir.